Crossing the Borders: Lived Experiences of Preschool Families during the Modular Distance Learning (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2024)
The sudden shift to modular learning brought about by the COVID-19 pandemic has presented a unique set of challenges and opportunities for children and their families. This study, which explored the family experiences in the preschool modular instructions, aimed to shed light on how families navigated this new learning landscape.Through a qualitative approach grounded in hermeneutic phenomenology, the study delved into the lived experiences of nine families with preschool students enrolled in modular learning. Unstructured interviews were conducted to gather insights into the challenges, frustrations, and unexpected benefits of this mode of instruction.The study’s findings revealed three key themes:• Challenges of Modular Learning: Families faced numerous challenges adapting to modular learning. These included:• Difficulties in understanding and implementing the curriculum: Parents often struggled to comprehend the learning materials and lacked the pedagogical expertise to guide their children’s learning effectively.• Limited access to resources and technology: Technological limitations and a lack of access to necessary resources, such as computers and reliable internet connectivity, further hindered learning.• Managing distractions and maintaining focus: Creating a conducive learning environment at home proved challenging, as children were often distracted by their surroundings and struggled to maintain focus during online lessons.• Parental Dissatisfaction with Preschool Distance Learning: Many parents expressed dissatisfaction with the lack of personalized attention and hands-on learning opportunities provided by distance learning. They felt ill-equipped to replace the role of trained educators and expressed concerns about the potential negative impact on their children's development.• Unexpected Benefits of Modular Learning: Some families identified unexpected benefits of modular learning despite the challenges. These included:• Strengthened family bonds: Learning fostered a sense of connection and collaboration between parents and children.• Enhanced parental involvement in education: Families better understood their children’s learning styles and needs, which could inform future educational decisions.• Development of new skills and strategies: Parents developed new skills, such as online research and creative teaching techniques, to support their children’s learning.Based on these findings, the study recommends several strategies to improve the effectiveness of modular learning for preschoolers:• Collaboration between Parents and Teachers: Fostering open communication and collaboration between parents and teachers can help bridge the gap between home and school, ensuring parents are well-equipped to support their children’s learning.• Regular Dialogue and Open Communication: Regular dialogue and open communication channels between parents and teachers can help identify and address any challenges or concerns that arise during the learning process.• Utilization of Social Platforms: Leveraging social platforms, such as Facebook groups or messaging apps, can create a supportive online community for parents to share experiences, seek advice, and connect with other families facing similar challenges.The sudden shift to modular learning has undoubtedly disrupted traditional education models and presented unique challenges for educators and families. However, by understanding the lived experiences of families and implementing the recommended strategies, we can work towards creating a more effective and supportive learning environment for preschoolers during these unprecedented times.
Keywords: Modular learning; COVID-19 pandemic; Preschool Family experiences; Challenges; Opportunities; Collaboration between parents and teachers; Regular dialogue and open communication; Social platforms